Low-cost, open-source contact angle analyzer using a mobile phone, commercial tripods and 3D printed parts. (October 2022) - Han, Won; Shin, Jaeho; Ho Shin, Joong
Graphical abstract: Abstract: Measurement of contact angle is important in many areas of science and engineering research. Contact angle analyzers are however not easily accessible due to their expensive cost, which hinders their use in research and also in education. In this study we propose a low-cost contact angle analyzer that can be assembled with 3D printed parts. Mobile phone is used for imaging, and the image is analyzed using an open-source ImageJ plugin. Commercial camera tripods are used as platform that provides movement in many degrees of freedom, which are important in leveling of the substrate and proper imaging of droplets. We utilize the tripods to build imaging modules, sample plate module and volume metering module, each of which perform distinct tasks. Especially, we characterize the usefulness of the volume metering module, which helps users dispense same volume of liquid to reduce human error during measurement. The cost of an analyzer is $255.10, which is an order of magnitude lower compared to commercial products. With the advancement in open source software and upgrades in the hardware modules, we expect that the proposed contact angle analyzer to have a positive impact in resource limited research labs and educational environments.